Overview of Variable Refrigerant Flow Air Conditioning System - Arfidian Rachman (Jurnal Teknik Mesin, 2021)
Variable refrigerant flow air-conditioning (VRF) systems are important and widely used in building energy systems around the world. The system is gradually gaining popularity in commercial and residential buildings due to its satisfactory partial load performance, flexible control, ease of installation and maintenance. Variable refrigerant flow air-conditioning (VRF) is a multi-split Heating, Ventilation and Air Conditioning (HVAC) system that controls refrigerant flow to control separate zones for the needs of residential consumers and commercial buildings. The objective of this review is to identify VRF systems that affect various aspects of operation and performance. Special VRF components regulate refrigerant volume control for system performance and reliability. The findings show that specific testing through different compressor settings, electronic expansion valve (EEV) position, and airflow operation affects performance, thermal comfort and potential energy savings. The main conclusions drawn from this detailed review provide a comprehensive overview of VRF and inspire new insights and viable solutions for relevant researchers, product developers, practitioners and policy makers in this field. Previous experimental investigations will be more helpful in the future direction of progress as the development of an extensive VRF system is still in the main stages.